Towards I4.0: A comprehensive analysis of evolution from I3.0. (June 2020) - Nakayama, Ruy Somei; de Mesquita Spínola, Mauro; Silva, José Reinaldo
Graphical abstract: Highlights: Industry 3.0: Centralized, monolithic and complex Manufacturing Systems. Industry 4.0: Distributed, modular and collaborative Manufacturing Systems. Overambitious Marketing confuses Technological Infrastructure with Possibilities. The Infrastructure to Technological Possibilities is under construction yet. Technological Possibilities on I3.0 cannot take full advantage of I4.0 platform yet. Abstract: Advances in Information Technology and Communications are leading to a paradigm shift in manufacturing automation systems. Based on the Internet of Things (IoT) and Smart Technologies, manufacturing industries are witnessing the fourth Industrial Revolution, coined as Industrie 4.0 (I4.0) . Although many studies related to this subject were published, including several literature reviews, there is no consensual definition of I4.0. Consequently, there is not a clear understanding of the underlying enabling technologies required to implement it. That makes it more difficult for players to plan a migration strategy. This paper proposes a technological pathway infrastructure from Industry 3.0 (I3.0) to I4.0, based on the analysis of research and academic involvement in this transition process. A bibliometric study was directed to academic work, while field research addressed industry practitioners. The purpose of field research is to understand the impact of the knowledge about the transition from I3.0 up to I4.0. The contribution of this study includes a construct showing the fundamental technology infrastructure to pave the way from I3.0 up to I4.0. Furthermore, it reveals the transition of manufacturing paradigm from I3.0 complex, centralized, monolithic architecture and physical Supply Chain to a modular, distributed, collaborative, and product-service-oriented I4.0 architecture.